How Does an Aerotropolis Integrate? A Case from Zhengzhou Airport Economy Zone - Baofeng Huo; Mengqiu Guo (Logistics, 2021)
As the modern aviation-oriented business model (aerotropolis), the Airport Economy Zone (AEZ) accumulates capital, technology, workforce, and other production factors. The AEZ always has a large number of infrastructure investments. Still, it has not yet achieved the expected effect in integrating and driving other regional resource endowments in the short term in China. Therefore, governments and AEZ organizations must utilize these investments and create values. This paper demonstrates how the Zhengzhou AEZ (ZAEZ) in China integrates its resources and stakeholders to overcome the remaining issues in its airport stage and gain competitive advantages. We classify three integrations: integrations from contents, including strategic alliance, information sharing, and process coordination; integrations from objectives, including internal integration and external integration; and integrations from objects, including integrating stakeholder, financial resource, and material resource. This paper presents the value creation and competitive advantages of the economy zone from the analysis of different integrations.